Analyzing Factors That Influence the Indonesia’s Gen Z in Reducing Food Waste - M Fariz Fadillah, Mardianto; Fajri Juli Rahman, Nur Zendrato; Suci, Rahmadani; Filzah, Syakirah (INTI International University, 2024)
Zero hunger is one of the goals that is still being realized in the Sustainable Development Goals (SDGs). With conditions in Indonesia, which currently occupies fourth place in the amount of food waste worldwide, with a weight reaching 20.93 tons per year. This is certainly a serious enough problem to realize sustainable development. Indonesia, which is currently dominated by Gen Z, certainly needs to pay more attention to this food waste so that it doesn't continue in the future. This problem makes it important to analyze the factors that influence Gen Z Indonesia in reducing food waste. This research aims to form a structural model that explains the factors that influence Gen Z in reducing food waste. The variables used in this research are the influence of social media content, millennial eating manners, food consumption efficiency, the role of social demographics, and commitment to reducing food waste. which was analyzed using the Structural Equation Modeling Partial Least Square (SEM-PLS) method. The research results show that the factors that influence Gen Z are the influence of social media content and the role of social demographics. Through this research, recommendations for activities related to efforts to reduce food waste based on SEM-PLS can be formulated to realize one of the goals of sustainable development.